2021
DOI: 10.1002/cche.10406
|View full text |Cite
|
Sign up to set email alerts
|

Effects of varying levels of succinylation and hydroxypropylation on functional, thermal and textural characteristics of white sorghum starch

Abstract: Background and objectives Starch is a versatile storage biopolymer with exceptional physicochemical properties. However, sometimes it owes certain functional inabilities in the native form which could be effectively overcome by chemical modifications to meet specific requirements. The present study was conducted to improve the functional properties of native sorghum starch chemically modifying via succinylation and hydroxypropylation. Native sorghum starch was modified with different concentrations of succinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Mehboob et al. ( 2021 ) also found an increase in the water holding capacity of sorghum starch due to the introduction of hydroxypropyl groups into the starch structure. Increased water uptake percentage of different starches due to the hydroxypropylation process has been reported by different researchers (Karim et al., 2008 ; Park & Kim, 2020 ; Tehkhunmag et al., 2008 ).…”
Section: Resultsmentioning
confidence: 94%
“…Mehboob et al. ( 2021 ) also found an increase in the water holding capacity of sorghum starch due to the introduction of hydroxypropyl groups into the starch structure. Increased water uptake percentage of different starches due to the hydroxypropylation process has been reported by different researchers (Karim et al., 2008 ; Park & Kim, 2020 ; Tehkhunmag et al., 2008 ).…”
Section: Resultsmentioning
confidence: 94%
“…In fact, low enthalpy demonstrates less stability of starch crystals and the structural order (Oh et al., 2019). Most studies on the modification of starch structures with hydroxypropylation process reported a decrease in the temperatures and enthalpy of gelatinization (Javadian et al., 2021; Mehboob et al., 2021; Oladebeye et al., 2019; Park & Kim, 2020; Shaikh et al., 2017; Wang & Shi, 2020). Tang et al.…”
Section: Resultsmentioning
confidence: 99%
“…However, at constant acid hydrolysis time, by increasing the propylene oxide ratio from 5% to 25%, the crystals and the structural order (Oh et al, 2019). Most studies on the modification of starch structures with hydroxypropylation process reported a decrease in the temperatures and enthalpy of gelatinization (Javadian et al, 2021;Mehboob et al, 2021;Oladebeye et al, 2019;Park & Kim, 2020;Shaikh et al, 2017;Wang & Shi, 2020). Tang et al (2012) also observed a decrease in gelatinization temperatures and enthalpy of acid-modified Kudzu root starch by hydroxypropylation process.…”
Section: The Pasting Propertiesmentioning
confidence: 99%